Design and behaviour of geosynthetic-reinforced soil walls constructed on yielding foundations. Issue 6 (December 2003) - Skinner, G. D.; Rowe, R. K.
Abstract : The short- and long-term behaviour of a 6 m high segmental block-faced geosynthetic-reinforced retaining wall constructed on a rigid base and two 10 m thick clay foundations (one relatively inviscous and one viscoplastic) were numerically investigated to assess the effect of yielding in the foundation deposit on the internal and external stability of the wall. The influence of the rate of loading on the undrained shear strength of the viscoplastic foundation clay deposit is examined. The overall short- and long-term behaviour of the reinforced soil wall, including reinforcement strains and deformations, are discussed and compared with the expected design values. It is shown that the viscoplastic nature of some clayey soils can cause a decrease in the undrained shear strength with time by as much as 20% and increase the reinforcement strains by as much as 45% relative to expected design values.